Solid-liquid two-phase electro-optic phase change energy-absorbing material, preparation method and application thereof

CN122941368APending Publication Date: 2026-10-20XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611434136.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]本申请旨在提供一种固液两相电致相变吸能材料及其制备方法与应用,以解决现有热耗散型过电压防护方案在瞬时能量密度、温升控制与重复可靠性方面不足的问题,使材料在脉冲电场下通过界面极化高效耗散脉冲能量的同时抑制贯通导电,并以液相实现热缓冲降温

Benefits of technology

1、本申请通过“硅铝酸盐骨架—原位二氧化钛纳米晶—绝缘界面层”三级多界面结构设计,使材料在脉冲电场下形成硅铝酸盐/二氧化钛、二氧化钛/绝缘界面层、颗粒/液相等多级界面,发生Maxwell-Wagner型界面极化与介电弛豫,构成以界面极化主导的高能量密度瞬时吸纳通道;同时绝缘界面层与高固含受限液相共同阻断载流子长程迁移,避免形成贯通导电通路,抑制电解、击穿与局部焦耳热集中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application discloses a solid-liquid two-phase electro-induced phase change energy-absorbing material, its preparation method, and its application, belonging to the field of electrical protection technology. The material comprises a 50 wt%~70 wt% solid phase component and a 30 wt%~50 wt% liquid phase component. The solid phase component consists of multi-interface composite particles, including an aluminosilicate framework, titanium dioxide nanocrystals grown in situ on their surface and / or in their channels, and a silica or silicate insulating interface layer coating the outer side of the titanium dioxide nanocrystals. The liquid phase component is a water-ethylene glycol composite liquid, filling the interparticle interface region to form a confined solid-liquid interface phase. Under a pulsed electric field, this material dissipates pulse energy through multi-level interfacial polarization and dielectric relaxation. The insulating interface layer and the confined liquid phase jointly suppress through-conduction conductivity, and the liquid phase provides nearby thermal buffering and cooling. This material can be used for pulse overvoltage protection in equipment such as converter valves, helping to solve the problems of low instantaneous energy density and temperature rise in existing heat dissipation solutions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrical protection technology, and in particular to a solid-liquid two-phase electro-induced phase change energy-absorbing material, its preparation method and application. Background Technology

[0002] Flexible power transmission and transformation equipment widely uses power electronic devices, which have lower overvoltage withstand capabilities than traditional electrical equipment. Taking converter valves as an example, under fault or operating conditions, they are subjected to short-term high-voltage pulses, and the accumulation of surplus energy on the order of tens of milliseconds can lead to overvoltage or even damage to the equipment. Therefore, there is a practical need for fast-absorbing energy protection materials that can be encapsulated within electrode elements and possess both high pulse energy absorption density and cooling buffering capabilities.

[0003] Existing overvoltage protection solutions mainly include metal oxide surge arresters, energy-dissipating resistors, and other heat dissipation devices. These solutions typically dissipate electrical energy through the heating of the device itself, which can limit overvoltage to a certain extent. However, they are insufficient in terms of instantaneous energy density, temperature rise control, and repeatability reliability. In space-constrained scenarios, they also suffer from problems such as heat concentration and temperature rise.

[0004] Beyond device-level solutions, some materials technologies are also being used for energy absorption or external field response scenarios. Phase change energy storage materials primarily utilize the latent heat of phase change to achieve thermal energy storage or temperature control. Their design specifications revolve around phase change temperature and latent heat, rather than directly addressing electrical response and temperature rise suppression under pulsed voltage. Electrorheological fluids or dielectric particle composite liquids disperse dielectric particles in a liquid phase, altering the system's rheological properties under an applied electric field. However, their technical objective is mechanical response control, rather than pulsed energy absorption and temperature rise reduction. Furthermore, existing research has dispersed aluminosilicate minerals and titanium dioxide composite particles in a liquid phase to form electrorheological fluids. This system exhibits enhanced electrorheological effects under an applied electric field, involving interfacial polarization and charge migration mechanisms. However, silicone oil is typically used as the liquid phase dispersion medium, resulting in a lack of insulation between dielectric particles. Under strong pulsed fields, this easily forms through-conductive pathways and generates localized Joule heat concentration, and it has not been directly used for low-temperature energy absorption under pulsed voltage.

[0005] Therefore, the technical problem that needs to be solved is how to provide a material system for short-term overvoltage and pulse energy impact conditions of flexible power transmission and transformation equipment such as converter valves, so that it can efficiently dissipate energy through interface polarization under pulse voltage while suppressing through-conduction conduction and achieving thermal buffering and cooling with liquid phase. Summary of the Invention

[0006] This application aims to provide a solid-liquid two-phase electro-phase change energy-absorbing material, its preparation method, and its application, in order to solve the problems of the shortcomings of existing heat dissipation type overvoltage protection schemes in terms of instantaneous energy density, temperature rise control, and repeatability reliability. The material can efficiently dissipate pulse energy through interface polarization under a pulsed electric field while suppressing through-conduction conductivity, and achieve thermal buffering and cooling in the liquid phase.

[0007] To achieve the above objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a solid-liquid two-phase electro-induced phase change energy-absorbing material, comprising a solid phase component and a liquid phase component; The solid phase component is a multi-interface composite particle, which includes an aluminosilicate framework, titanium dioxide nanocrystals grown in situ on the surface and / or in the channels of the aluminosilicate framework, and an insulating interface layer covering the outside of the titanium dioxide nanocrystals. The insulating interface layer is a silicon dioxide layer or a silicate layer. The liquid phase component is a water-ethylene glycol compound solution; The solid phase component has a content of 50 wt% to 70 wt%, and the liquid phase component has a content of 30 wt% to 50 wt%. The liquid phase component fills the interfacial region between the multi-interface composite particles, forming a confined solid-liquid interfacial phase with the multi-interface composite particles.

[0008] In the above technical solution, the aluminosilicate framework provides mechanical support, a large specific surface area, and natural confined space; the titanium dioxide nanocrystals are firmly bonded to the framework and uniformly dispersed through in-situ growth, serving as a high dielectric constant functional crystalline phase. Under a pulsed electric field, they generate strong interfacial polarization and dielectric relaxation energy dissipation, acting as the core of energy absorption; the insulating interface layer blocks direct contact between titanium dioxide nanocrystals, raising the through-conduction threshold, suppressing leakage conduction and local Joule heat concentration, and simultaneously forming another level of polarization interface. In a high solid content system with a solid phase composition of 50 wt%~70 wt%, the liquid phase no longer exists as a continuous phase but is confined to the interfacial region between multi-interface composite particles: on the one hand, it maximizes the solid-liquid interface area and significantly increases the density of interfacial polarization sites; on the other hand, the carrier migration path is physically blocked, suppressing electrolysis, breakdown, and through-conduction conduction; simultaneously, the liquid phase is distributed in a thin film form around the energy-absorbing phase, which can quickly absorb the heat generated by pulse dissipation nearby and suppress local hot spots. If the solid content is less than 50 wt%, the interfacial density is insufficient, the energy absorption density decreases, and the particles are prone to sedimentation and stratification; if it is higher than 70 wt%, the system loses its fluidity, filling and degassing become difficult, and the liquid phase thermal buffering function is weakened.

[0009] Furthermore, the aluminosilicate framework is a layered aluminosilicate, which is selected from at least one of kaolin, montmorillonite, mica, and attapulgite, with kaolin being preferred.

[0010] Furthermore, the mass of the titanium dioxide nanocrystals accounts for 10 wt% to 40 wt% of the total mass of the aluminosilicate framework and the titanium dioxide nanocrystals, preferably 10 wt% to 30 wt%, more preferably 20 wt%; the crystal form of the titanium dioxide nanocrystals is anatase, rutile, or a combination thereof.

[0011] In this application, the content of titanium dioxide nanocrystals is based on the total mass of aluminosilicate and titanium dioxide in the aluminosilicate / titanium dioxide composite powder without silicon source interface treatment, that is, the mass percentage of titanium dioxide in the total mass of aluminosilicate and titanium dioxide; the mass of silicon-oxygen-containing structures added after silicon source interface treatment is not included in the calculation basis of titanium dioxide nanocrystal content.

[0012] Furthermore, the insulating interface layer is formed by hydrolysis and condensation of a silicon source, wherein the silicon source is selected from at least one of sodium silicate, silica sol, tetraethyl orthosilicate, and potassium silicate.

[0013] Furthermore, the median particle size D50 of the multi-interface composite particles is 0.5 μm to 20 μm.

[0014] Furthermore, the mass ratio of water to ethylene glycol in the water-ethylene glycol compound solution is 1:9 to 7:3.

[0015] Furthermore, the content of the solid phase component is 57 wt% to 63 wt%, preferably 60 wt%.

[0016] Secondly, this application provides a method for preparing a solid-liquid two-phase electro-induced phase change energy-absorbing material, comprising the following steps: S1: Pre-treat the aluminosilicate raw material to obtain aluminosilicate framework powder; S2: The aluminosilicate framework powder is dispersed in a titanium source hydrolysis system, and after hydrolysis, aging and calcination crystallization, titanium dioxide nanocrystals are grown in situ on the surface and / or pores of the aluminosilicate framework powder to obtain aluminosilicate-titanium dioxide composite particles. S3: The aluminosilicate-titanium dioxide composite particles are hydrolyzed and condensed to form an insulating interface layer on the outside of the titanium dioxide nanocrystals using a silicon source, and then dried to obtain multi-interface composite particles. S4: The multi-interface composite particles are mixed with a water-ethylene glycol compound solution, and after shear dispersion and vacuum degassing, a solid-liquid two-phase electro-phase change energy-absorbing material with a solid component content of 50 wt%~70 wt% is obtained.

[0017] Furthermore, in step S2, the titanium source in the titanium source hydrolysis system is tetrabutyl titanate or titanium oxysulfate; the loading, crystal ratio and grain size of the titanium dioxide nanocrystals are controlled by adjusting the titanium source concentration, hydrolysis pH, aging time and calcination temperature.

[0018] Furthermore, in step S3, the silicon source is sodium silicate or tetraethyl orthosilicate; the thickness of the insulating interface layer is controlled by adjusting the amount of silicon source and the hydrolysis conditions.

[0019] Further, in step S4, the multi-interface composite particles are first pre-mixed with ethylene glycol for pre-wetting, and the amount of ethylene glycol is 10% to 40% of the total mass of the liquid phase components. Then, water-ethylene glycol compound solution is added to the pre-wetted multi-interface composite particles in steps.

[0020] Thirdly, the solid-liquid two-phase electro-phase change energy-absorbing material provided in this application is used in converter valves, flexible power transmission and transformation equipment, power electronic devices, pulse overvoltage protection devices, or overvoltage protection of electrical equipment. The application is to absorb short-time pulse electrical energy and reduce the local temperature rise of the device.

[0021] Furthermore, the application is to absorb short-term pulse electrical energy generated by the converter valve during faults, operation, or commutation, and to reduce the local temperature rise of the device.

[0022] Furthermore, this application provides a pulse energy absorption element, including multiple layers of spaced metal plates, with a confined energy absorption cavity formed between adjacent metal plates, the confined energy absorption cavity being filled with the solid-liquid two-phase electro-phase change energy absorption material described in the first aspect; each of the metal plates is electrically connected to a first external lead and a second external lead according to alternating polarities, so that each of the confined energy absorption cavities is electrically connected in parallel.

[0023] Furthermore, the spacing between adjacent metal plates is 5 mm to 20 mm, preferably 8 mm to 12 mm, and more preferably 10 mm.

[0024] Compared with the prior art, this application has the following beneficial effects: 1. This application adopts a three-level multi-interface structure design of "aluminosilicate framework - in-situ titanium dioxide nanocrystals - insulating interface layer" to enable the material to form multi-level interfaces such as aluminosilicate / titanium dioxide, titanium dioxide / insulating interface layer, and particle / liquid phase under pulsed electric field, and Maxwell-Wagner type interface polarization and dielectric relaxation occur, forming a high energy density instantaneous absorption channel dominated by interface polarization; at the same time, the insulating interface layer and the high solid content confined liquid phase jointly block the long-range migration of charge carriers, avoid the formation of through conductive pathways, and suppress electrolysis, breakdown and local Joule heat concentration.

[0025] 2. This application uses a water-ethylene glycol compound as the liquid phase. Water provides a polar solid-liquid interface and high specific heat thermal buffering capacity, while ethylene glycol increases the boiling point and anti-volatilization capacity of the liquid phase, reducing the risk of liquid phase loss, bubble formation and interface instability under pulsed temperature rise conditions, and ensuring working stability over a wide temperature range. The liquid phase is confined in the interparticle interface region to form a restricted solid-liquid interface phase, which maximizes the density of interfacial polarization sites, restricts charge migration, and homogenizes thermal buffering. The three factors work together to maintain the stability of the material under repeated pulses.

[0026] 3. This application adopts a stepwise addition method of ethylene glycol pre-wetting and water-ethylene glycol compound solution, so that ethylene glycol is preferentially distributed on the surface of composite powder, in pores and near the insulating interface layer, and then gradually constructs a high solid content confined liquid phase, which is beneficial to reduce particle agglomeration, bubble encapsulation and free liquid phase ratio. Attached Figure Description

[0027] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic flowchart illustrating a method for preparing a solid-liquid two-phase electro-induced phase change energy-absorbing material according to one embodiment of this application. Figure 2 The dielectric constant and dielectric loss spectra of SiAl / TiO2 with different solid filler mass fractions provided in this application; Figure 3 This application provides Cole-Cole diagrams of complex conductivity for SiAl / TiO2 with different solid filler mass fractions. Figure 4 The dielectric constant and dielectric loss spectrum of SiAl / TiO2 composite powders with different TiO2 contents provided in this application; Figure 5 Cole-Cole plots showing the equivalent series resistance and complex conductivity of samples with different TiO2 contents; Figure 6 X-ray diffraction (XRD) patterns of the E1 and C1 samples provided in this application; Figure 7 Scanning electron microscope (SEM) images of E1, C1 samples and TiO2 provided for this application; Figure 8 Fourier transform infrared (FTIR) spectra of aluminosilicate, TiO2, and E1 and C1 samples provided for this application; Figure 9 A comparison diagram of AC breakdown of the E1, C1, and C2 packaged components provided in this application; Figure 10The voltage cycling stability test results of the packaged components E1, C1 and C2 provided in this application; Figure 11 This is a physical diagram of an optional solid-liquid two-phase electro-phase change energy-absorbing element in an embodiment of this application. Detailed Implementation

[0028] To enable those skilled in the art to better understand the technical solutions of this application, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative of this application and are not intended to limit the scope of this application.

[0029] In this application, "electro-induced phase transition" refers to a material transforming from a flowable or semi-flowable state to an apparent solid state with higher apparent viscosity, yield stress, or storage modulus under the action of a pulsed electric field; after the electric field is removed, the material returns to a flowable or semi-flowable state. This process is a reversible electrorheological state transition and does not belong to thermodynamic melting or solidification phase transition.

[0030] In this application, "confined solid-liquid interface phase" refers to a solid-liquid composite phase formed in a solid-liquid two-phase system with high solid content, where the liquid phase no longer exists as a continuous phase but is confined to the interface region between solid particles.

[0031] In this application, "in-situ growth" refers to the process by which titanium source is hydrolyzed, deposited, condensed, aged, and calcined in the surface and / or channels of the aluminosilicate framework to directly form titanium dioxide nanocrystals on the framework. The titanium dioxide nanocrystals form chemical bonds or strong interfacial bonds with the aluminosilicate framework, rather than a simple physical mixture of two independent powders.

[0032] In this application, "median particle size D50" refers to the particle size corresponding to a cumulative particle size distribution percentage of 50%, which can be determined by a laser particle size analyzer using conventional methods.

[0033] In some embodiments, a solid-liquid two-phase electro-induced phase change energy-absorbing material is provided, comprising a solid phase component and a liquid phase component. The solid phase component is a multi-interface composite particle, comprising an aluminosilicate framework, titanium dioxide nanocrystals grown in situ on the surface and / or channels of the aluminosilicate framework, and an insulating interface layer coating the outside of the titanium dioxide nanocrystals, the insulating interface layer being a silicon dioxide layer or a silicate layer. The liquid phase component is a water-ethylene glycol mixture. The content of the solid phase component is 50 wt%~70 wt%, and the content of the liquid phase component is 30 wt%~50 wt%. The liquid phase component fills the interface region between the multi-interface composite particles, forming a confined solid-liquid interface phase.

[0034] In the above composition, the aluminosilicate framework provides mechanical support, a large specific surface area, and natural confined space. Titanium dioxide nanocrystals, through in-situ growth, are firmly bonded to the framework and uniformly dispersed. As a high-dielectric-constant functional crystalline phase, they generate interfacial polarization and dielectric relaxation energy dissipation under a pulsed electric field, serving as the core energy-absorbing component. The insulating interface layer blocks direct contact between titanium dioxide nanocrystals, raising the through-conduction threshold, suppressing leakage conduction and local Joule heat concentration, while simultaneously forming another level of polarization interface. Thus, under a pulsed electric field, the material forms multiple levels of interfaces, including aluminosilicate / titanium dioxide, titanium dioxide / insulating interface layer, and particle / liquid phase, resulting in Maxwell-Wagner type interfacial polarization and dielectric relaxation, converting electric field energy into dielectric loss heat, forming the main channel for pulsed energy dissipation.

[0035] In high-solids systems with a solid content of 50 wt%–70 wt%, the liquid phase no longer exists as a continuous phase but is confined to the interfacial region between multi-interface composite particles. This maximizes the solid-liquid interface area and increases the density of interfacial polarization sites. Furthermore, the physical blockage of carrier migration paths helps suppress electrolysis, breakdown, and conduction. Simultaneously, the liquid phase, distributed as a thin film around the energy-absorbing phase, can absorb heat generated by pulse dissipation nearby, suppressing local hot spots. If the solid content is below 50 wt%, the solid-liquid interface density is insufficient, the energy absorption density decreases, and particles easily settle and stratify. If the solid content is above 70 wt%, the system loses its fluidity, filling and degassing become difficult, and the liquid phase's thermal buffering function weakens.

[0036] Furthermore, the aluminosilicate framework is a layered aluminosilicate, which is selected from at least one of kaolin, montmorillonite, mica, and attapulgite, with kaolin being preferred. The lamellar and porous structure of the layered aluminosilicate provides a carrier and confined space for the in-situ growth of titanium dioxide nanocrystals, and it is widely available, low in cost, and has good thermal stability.

[0037] Furthermore, the mass of titanium dioxide nanocrystals accounts for 10 wt% to 40 wt% of the total mass of the aluminosilicate framework and titanium dioxide nanocrystals, preferably 10 wt% to 30 wt%, and more preferably 20 wt%. The crystal form of the titanium dioxide nanocrystals is anatase, rutile, or a combination thereof, preferably anatase.

[0038] In this application, the content of titanium dioxide nanocrystals is based on the total mass of aluminosilicate and titanium dioxide in the aluminosilicate / titanium dioxide composite powder without silicon source interface treatment, that is, the mass percentage of titanium dioxide in the total mass of aluminosilicate and titanium dioxide; the mass of silicon-oxygen-containing structures added after silicon source interface treatment is not included in the calculation basis of titanium dioxide nanocrystal content.

[0039] The loading and crystal form of titanium dioxide determine the dielectric constant and interfacial polarization intensity of the material: if the loading is too low, the contribution of polarization energy consumption is insufficient; if the loading is too high, the difficulty of interparticle insulation increases, the distance between adjacent titanium dioxide nanocrystals shortens, interfacial charge accumulation and local charge migration are enhanced, and the risk of through-conduction conductivity increases. In the embodiments of this application, the titanium dioxide content is calculated based on the total mass of the aluminosilicate and titanium dioxide composite powder before silicon source coating treatment (i.e., the mass percentage of titanium dioxide in the total mass of aluminosilicate and titanium dioxide).

[0040] The insulating interface layer is formed by the hydrolysis and condensation of a silicon source, which is selected from at least one of sodium silicate, silica sol, tetraethyl orthosilicate, and potassium silicate. The insulating interface layer at least partially covers the surface of the composite particles or is distributed between adjacent titanium dioxide nanocrystals. It reduces the probability of direct contact between titanium dioxide nanocrystals forming a continuous conductive path, while simultaneously improving the surface wettability and particle dispersibility of the composite powder. If the insulating interface layer is too thin, the insulation will be insufficient; if it is too thick, it will weaken the polarization coupling between the titanium dioxide crystalline phase and the liquid phase, reducing the energy absorption capacity per unit volume.

[0041] Structural characterization indicates that the insulating interface layer exists primarily in an amorphous or hypocrystalline state: no characteristic diffraction peaks of crystalline silica were observed in the X-ray diffraction spectrum, while the characteristic diffraction peaks of crystalline silica were observed at approximately 900 cm⁻¹ in the Fourier transform infrared spectrum. - ¹~1200 cm - The relatively enhanced Si-O related absorption within the range ¹, accompanied by peak broadening, indicates that the silicon source hydrolysis and condensation introduces silicon-oxygen-containing structures on the surface and / or between particles of the composite powder.

[0042] Furthermore, the liquid phase component is a water-ethylene glycol composite solution. More specifically, the mass ratio of water to ethylene glycol in the water-ethylene glycol composite solution is 1:9 to 7:3. Water provides a high specific heat capacity and a strongly polar dielectric environment, serving as a thermal buffer and cooling agent; ethylene glycol is used to increase the boiling point and anti-volatility of the liquid phase component, reducing the risk of liquid phase volatilization, bubble formation, and interfacial instability caused by localized temperature rise during pulsed energy absorption, thereby ensuring operational stability and filling processability over a wide temperature range (especially at low temperatures).

[0043] Furthermore, the median particle size D50 of the multi-interface composite particles is 0.5 μm to 20 μm. Particle size affects the solid-liquid interface area, sedimentation stability, and filling processability: if the particle size is too large, the interface area per unit mass decreases, and the risk of sedimentation increases; if the particle size is too small, the powder is prone to agglomeration, and the difficulty of dispersion and degassing increases.

[0044] Further, the content of the solid phase component is 57 wt%~63 wt%, and the content of the liquid phase component is 37 wt%~43 wt%; more preferably, the content of the solid phase component is 60 wt%, and the content of the liquid phase component is 40 wt%. When the solid phase content deviates from 60 wt%, the pulse energy absorption temperature rise shows an increasing trend. The reason is that when the solid phase content is too low, the number of solid-liquid two-phase interfaces is insufficient, and the contribution of interfacial polarization to energy dispersion and absorption is limited; when the solid phase content is too high, the spacing between solid phase particles decreases, the probability of mutual contact increases, and local conductive channels are easily formed, resulting in increased dielectric loss and Joule heating.

[0045] In some embodiments, refer to Figure 1 A method for preparing a solid-liquid two-phase electro-induced phase change energy-absorbing material is provided, comprising the following steps: S1: Pre-treat the aluminosilicate raw material to obtain aluminosilicate framework powder; S2: Disperse aluminosilicate framework powder in a titanium source hydrolysis system, and after hydrolysis, aging and calcination crystallization, titanium dioxide nanocrystals are grown in situ on the surface and / or pores of the aluminosilicate framework powder to obtain aluminosilicate-titanium dioxide composite particles. S3: A silicon source is used to hydrolyze and condense the aluminosilicate-titanium dioxide composite particles to form an insulating interface layer on the outside of the titanium dioxide nanocrystals. After drying, multi-interface composite particles are obtained. S4: Mix the multi-interface composite particles with a water-ethylene glycol compound solution, and then perform shear dispersion and vacuum degassing to obtain a solid-liquid two-phase electro-phase change energy-absorbing material with a solid component content of 50 wt%~70 wt%.

[0046] In the above preparation method, the in-situ growth in step S2 improves the bonding strength and dispersion uniformity between titanium dioxide and the framework; the thin-layer coating in step S3 ensures insulation between particles; within the target pulsed electric field range, the energy dissipation of the material is mainly due to interface polarization and dielectric relaxation loss, and the probability of through-conductivity and local Joule heat concentration is reduced.

[0047] In some embodiments, a specific implementation of step S1 is provided as follows: The aluminosilicate raw material is subjected to washing, dispersion, sedimentation classification, filtration and drying to remove coarse particles and soluble impurities, resulting in aluminosilicate powder with a relatively uniform particle size distribution.

[0048] Aluminosilicate powders can be further activated by acid or alkali to increase surface hydroxyl groups, pore structure, and active adsorption sites. Acid activators can be hydrochloric acid, sulfuric acid, nitric acid, or combinations thereof; alkali activators can be sodium hydroxide, potassium hydroxide, or combinations thereof. After activation, the aluminosilicate powders are washed, dried, and ground to obtain a surface-activated aluminosilicate support framework.

[0049] In one specific embodiment, 600 g of aluminosilicate raw material was added to 1200 mL of deionized water and stirred at 800 r / min for 10 min; after settling for 120 min, the upper and middle layers of suspension were filtered. Acid activation was performed using hydrochloric acid at a concentration of 1 mol / L, with a mass ratio of aluminosilicate to hydrochloric acid of 1:3, at 25 ℃ for 1 h. After activation, the filtrate was washed with deionized water until the pH reached 5-6 to prevent residual acid from continuously corroding the framework during drying; it was dried at 80 ℃ for 6 h, and then ball-milled for 30 min. The ball milling was performed intermittently (milling for 10 min and stopping for 5 min) to prevent local overheating of the milling chamber and reduce secondary agglomeration of fine particles; after ball milling, the material was passed through a 300-mesh standard sieve to remove a small amount of large particle agglomerates, resulting in an aluminosilicate support framework with a D50 of 2 μm-5 μm.

[0050] Furthermore, in some embodiments, a specific implementation of step S2 is provided as follows: Aluminosilicate framework powder is dispersed in a reaction system containing a titanium source, so that the titanium source undergoes hydrolysis, deposition, condensation or crystallization on the surface and / or in the channels of aluminosilicate to form a titanium dioxide functional phase.

[0051] Furthermore, the titanium source in the titanium source hydrolysis system is tetrabutyl titanate or titanium oxysulfate; the loading, crystal ratio, and grain size of titanium dioxide nanocrystals are controlled by adjusting the titanium source concentration, hydrolysis pH, aging time, and calcination temperature. In other embodiments, the titanium source may also be selected from isopropyl titanate, titanium tetrachloride, or combinations thereof; the treatment methods include hydrolysis, sol-gel, low-temperature hydrothermal treatment, precipitation, aging, calcination, or combinations thereof.

[0052] In one specific embodiment, 400 g of pretreated aluminosilicate framework powder (D50 of 2 μm to 5 μm, passed through a 300-mesh sieve) was dispersed in 3600 g of a composite controlled reaction medium. The composite controlled reaction medium consisted of 3200 g of anhydrous ethanol, 200 g of deionized water, and 200 g of glacial acetic acid. The powder was initially dispersed by mechanical stirring at 400 r / min for 10 min, followed by ultrasonic dispersion at 200 W for 30 min in a 40℃ water bath to ensure complete deagglomeration and the absence of visible clumps. The pH of the suspension was adjusted dropwise to 2-3 using 0.1 mol / L dilute hydrochloric acid, and the mixture was stirred stably for 5 min to confirm no pH fluctuations. Add 424 g of titanium source, which is tetrabutyl titanate (TBOT, chemically pure). The titanium source was pre-diluted with 800 mL of anhydrous ethanol and transferred to a constant pressure dropping funnel. It was added slowly dropwise at a rate of 40 mL / min to 80 mL / min, while maintaining a 40 ℃ water bath and stirring at 400 r / min throughout the process. After the addition was complete, the system was kept at a constant temperature of 40 ℃ for 2 h to hydrolyze the mixture. After the reaction was completed, the stirring was turned off, and the mixture was allowed to stand at the same temperature for 3 h to strengthen the interfacial bonding between titanium dioxide and the framework. The resulting product was separated by filtration. The filter cake was washed twice with anhydrous ethanol (approximately 50 mL each time) to remove residual organic matter, and then repeatedly washed with deionized water until the pH of the filtrate stabilized at 5-6. The filter cake (with a thickness not exceeding 2 cm) was then dried in a forced-air dryer at 80 ℃ for 6 h. When preparing anatase titanium dioxide by crystallization, the dried powder is transferred to an alumina crucible and calcined at 450 °C for 2.5 h in air at a heating rate of 2 °C / min. After natural cooling, it is removed to obtain aluminosilicate-titanium dioxide composite particles (aluminosilicate / TiO2 composite powder). Based on the theoretical calculation of the above feed amount, the theoretical TiO2 formed after the reaction of 400 g of aluminosilicate and 424 g of tetrabutyl titanate is approximately 99.5 g, and the theoretical TiO2 content is approximately 19.9 wt%, which is basically consistent with the target loading of 20 wt%.

[0053] Furthermore, in some embodiments, a specific implementation of step S3 is provided as follows: Aluminosilicate-titanium dioxide composite particles are added to a silicon source treatment solution and then subjected to wetting, hydrolysis, deposition, condensation, drying or heat treatment to form an insulating interface layer containing silicon-oxygen structure on the surface of the composite particles and / or between titanium dioxide nanocrystals.

[0054] Furthermore, the silicon source is sodium silicate or tetraethyl orthosilicate; the thickness of the insulating interface layer is controlled by adjusting the amount of silicon source and hydrolysis conditions. In other embodiments, the silicon source may also be selected from silica sol, potassium silicate, or a combination thereof. After treatment, the powder is dried, ground, and sieved to obtain surface-controlled aluminosilicate / TiO2 composite powder, i.e., multi-interface composite particles.

[0055] In one specific embodiment, 400 g of aluminosilicate / TiO2 composite powder (D50 of 2 μm to 5 μm, TiO2 loading of 20 wt%) was added to 3800 g of a basic dispersion solution, which consisted of 3400 g of anhydrous ethanol and 400 g of deionized water. The powder was initially dispersed by mechanical stirring at 350 r / min for 10 min, followed by ultrasonic dispersion at 200 W for 20 min in a 35 ℃ water bath to ensure complete deagglomeration and the absence of visible clumps. The pH of the system was adjusted dropwise to 8 to 9 using concentrated ammonia (25% to 28% by mass), and the mixture was stirred stably for 5 min to confirm no pH fluctuations. The total amount of silicon source used was 70 g, and the silicon source was tetraethyl orthosilicate (TEOS, analytical grade). The silicon source was pre-diluted with 400 mL of anhydrous ethanol and transferred to a constant pressure dropping funnel. It was added to the treatment solution slowly, with the dropping rate controlled at 40 mL / min to 80 mL / min. The entire process was carried out in a 35 ℃ water bath with stirring at 350 r / min. After the addition was completed, the solution was treated at 35 ℃ with stirring at 600 r / min for 2 h. Then the reaction was stopped, and the solution was separated by vacuum filtration. The filter cake was first washed twice with anhydrous ethanol (about 50 mL each time), and then repeatedly washed with deionized water until the pH of the filtrate stabilized at 6-7. The washed filter cake (material layer thickness not exceeding 2 cm) was dried in a forced-air environment at 80 ℃ for 6 h; then it was transferred to an alumina crucible and heat-treated at 450 ℃ for 2 h in an air atmosphere at a heating rate of 2 ℃ / min. After natural cooling, it was removed; after light grinding and passing through a 300-mesh standard sieve, surface-controlled aluminosilicate / TiO2 composite powder was obtained, with a final mass of approximately 408 g~416 g.

[0056] In the above embodiments, 450 ℃ was selected as the uniform calcination temperature, which is the balance point of thermal stability among the aluminosilicate carrier, TiO2 functional phase, and SiO2 insulating interface layer: For TiO2, its amorphous precursor begins to crystallize at 350 ℃, and at 450 ℃ it can be completely transformed into the anatase phase with a grain size of 10 nm to 20 nm, which is much lower than the anatase-rutile phase transformation temperature of 600 ℃, and no grain agglomeration or crystal form deterioration will occur; For kaolin aluminosilicate, 450 ℃ is lower than its significant dehydroxylation initiation temperature of 480 ℃, avoiding the severe dehydroxylation range of 550 ℃ to 650 ℃, and can completely preserve the layered porous framework structure; For the SiO2 shell, this temperature can promote the precursor to fully dehydrate and condense, forming a dense and stable amorphous insulating network without the risk of cracking. If the temperature is below 400 ℃, the transformation of both phase precursors is insufficient, resulting in a large amount of residual organic matter and a loose structure; if the temperature is above 500 ℃, it will cause the collapse of the aluminosilicate framework, significant growth of TiO2 grains, and stress cracking in the SiO2 shell.

[0057] Furthermore, in some embodiments, a specific implementation of step S4 is provided as follows: Multi-interface composite particles were mixed with a water-ethylene glycol compound solution, and then subjected to shear dispersion and vacuum degassing treatment to obtain a solid-liquid two-phase electro-phase change energy-absorbing material with a solid component content of 50 wt%~70 wt%.

[0058] Further, in step S4, the multi-interface composite particles are first pre-mixed with ethylene glycol for pre-wetting. The amount of ethylene glycol used for pre-wetting is 10% to 40% of the total mass of the liquid phase components. Then, a water-ethylene glycol compound solution is added to the pre-wetted multi-interface composite particles in steps. By using ethylene glycol pre-wetting and step-by-step liquid addition, ethylene glycol is preferentially distributed on the surface of the composite powder, in the pores, and near the insulating interface layer. This gradually constructs a high-solids-content confined liquid phase, which helps to reduce particle agglomeration, bubble encapsulation, and the proportion of free liquid phase.

[0059] In one specific embodiment, mixing and degassing are performed as follows: (1) Pre-wetting of the interface with ethylene glycol: Take 400 g of surface-controlled aluminosilicate / TiO2 composite powder (D50 is 2 μm~5 μm, passed through a 300-mesh sieve), add 80 g of ethylene glycol (analytical grade), the amount of which accounts for 30% of the total mass of the final liquid phase. First, manually stir with a glass rod until there are no obvious dry powder lumps, then transfer it to a vacuum stirring vessel with water bath temperature control; under the conditions of temperature 30 ℃ and vacuum degree -85kPa (gauge pressure), mechanically stir at a low speed of 300 r / min for 20 min; during the stirring process, perform intermittent ultrasonication once every 5 min, each time for 1 min, with an ultrasonic power of 200 W, so that ethylene glycol preferentially penetrates into the internal pores, particle surface and near the insulating interface layer of the composite powder under negative pressure, replacing the air in the pores. The processed sample appears as a uniform, moist, loose powder with an overall matte, moist state. It can be clumped when squeezed but crumbles easily when touched. There are no white dry powder areas, no obvious dry powder or hard agglomerates, and no large air bubbles are visible to the naked eye after vacuum degassing. Only a very small number of micron-sized microbubbles are present.

[0060] (2) Stepwise addition of water-ethylene glycol compound solution: Prepare each water-ethylene glycol compound solution according to Table 1, and add it in 3 separate steps, maintaining a water bath temperature of 30 ℃ throughout the process; after each addition, scrape off the powder adhering to the container wall and the stirring / shear head before starting the shear dispersion. In this embodiment, the final liquid phase consists of deionized water and ethylene glycol in a mass ratio of 1:1, with 134 g of each, and a total liquid phase mass of 268 g; 80 g of ethylene glycol has been added in the pre-wetting stage, and the remaining 54 g of ethylene glycol and 134 g of deionized water are added in the stepwise addition stage. The amount of liquid added and the shear parameters are shown in Table 1 below: Table 1. Liquid addition volume and shear parameters for each addition

[0061] By controlling the number of liquid additions, the liquid addition interval, the shear rate, and the mixing time, the liquid phase gradually enters the gaps and pore regions between the composite particles, forming a solid-liquid two-phase system with a solid content of 50 wt% to 70 wt%. In this embodiment, after mixing 400 g of composite powder with 268 g of liquid phase, the total mass of the material is approximately 668 g, and the final solid content is approximately 60 wt%.

[0062] (3) Degassing and Encapsulation: Approximately 668 g of the obtained material was placed under a vacuum of -90 kPa (gauge pressure) for 10 min to remove bubbles formed during mixing and filling. After degassing, no bubbles were visible to the naked eye, and the slurry cross-section was dense and uniform, without obvious pores or cavity defects. The degassed material can be filled into pulse energy-absorbing elements and sealed, or used for structural characterization and electrical testing.

[0063] In some embodiments, the above-described solid-liquid two-phase electro-phase change energy-absorbing material is provided for use in converter valves, flexible power transmission and transformation equipment, power electronic devices, pulse overvoltage protection devices, or overvoltage protection of electrical equipment. This application is to absorb short-time pulse electrical energy and reduce the local temperature rise of the device.

[0064] Furthermore, this application aims to absorb short-term pulsed electrical energy generated by the converter valve during faults, operation, or commutation processes, and reduce the local temperature rise of the device. When the converter valve is subjected to short-term high-voltage pulses under fault or operational conditions, the accumulation of surplus energy on the order of tens of milliseconds can lead to overvoltage or even damage to the equipment. The material in this application dissipates pulsed energy through multi-stage interface polarization and dielectric relaxation under a pulsed electric field, while simultaneously achieving local thermal buffering with a confined liquid phase, making it suitable for overvoltage protection under the aforementioned operating conditions.

[0065] In one embodiment, a pulse energy absorption element is provided, comprising multiple layers of spaced metal plates, with a confined energy absorption cavity formed between adjacent metal plates, the confined energy absorption cavity being filled with the aforementioned solid-liquid two-phase electro-phase change energy absorption material; each metal plate is electrically connected to a first external lead and a second external lead according to alternating polarities, so that each confined energy absorption cavity is electrically connected in parallel.

[0066] Furthermore, the spacing between adjacent metal plates is 5 mm to 20 mm, preferably 8 mm to 12 mm, and more preferably 10 mm. If the spacing is too small, the local electric field strength near the electrode is high, increasing the risk of local breakdown, electrolysis, and bubble bridging; if the spacing is too large, the internal electric field strength of the material decreases under the same applied voltage, reducing the energy dissipation efficiency of interface polarization and dielectric relaxation. Multilayer plates combined with the above-mentioned spacing can achieve a balance between withstand voltage stability, energy absorption efficiency, and engineering packaging feasibility.

[0067] In some embodiments, the pulse energy-absorbing element includes an insulating housing, multilayer metal plates, a solid-liquid two-phase electro-phase change energy-absorbing material, an insulating spacer structure, a sealing structure, an external lead-out terminal, and a fixing structure, for encapsulating the solid-liquid two-phase electro-phase change energy-absorbing material to form an electrical component that can be installed, led out, and connected to a pulse protection circuit.

[0068] (1) Insulating Housing: The overall dimensions of the insulating housing are approximately 200 mm × 100 mm × 70 mm. An internal sealed encapsulation cavity is provided, with internal dimensions of approximately 150 mm × 80 mm × 50 mm. The insulating housing includes a housing body and a housing cover plate. The housing body is made of polytetrafluoroethylene (PTFE) sheet. PTFE has good electrical insulation, corrosion resistance, temperature resistance, and low water absorption, providing insulating support, mechanical constraint, and sealing space for water-glycol-based solid-liquid two-phase materials. The insulating housing may also include an electrode mounting groove, a PTFE insulating spacer frame, an exhaust port, an external lead-out mounting hole, a sealing ring mounting groove, and a housing fixing hole. After material filling and degassing, the filling port and exhaust port are sealed with threaded plugs, gaskets, and sealant.

[0069] (2) Multilayer metal plates: Seven parallel metal plates are arranged sequentially along the 80 mm direction of the encapsulation cavity. The dimensions of each metal plate are 138 mm in length × 48 mm in width × 1 mm in thickness. The metal plates are made of 316L stainless steel, which has good conductivity, mechanical strength and corrosion resistance, and good encapsulation compatibility with the water-ethylene glycol solid-liquid two-phase system. The spacing between adjacent metal plates is 10 mm, and a confined energy absorption cavity is formed between each two adjacent metal plates, forming a total of 6 confined energy absorption cavities. The theoretical dimension occupied by the 7 plates and the 6 plate spacings along the arrangement direction is 67 mm. The internal dimension of the encapsulation cavity along the plate arrangement direction is 80 mm. After the plate assembly is installed, there is about 13 mm of space remaining along this direction, which can be used to set the housing mounting slot, insulation spacer structure and assembly allowance. Adjacent metal plates are kept at a fixed distance by polytetrafluoroethylene insulating spacer frames, insulating support columns or housing mounting slots to prevent the plates from moving, tilting or directly contacting each other.

[0070] (3) Electrode Connection Method: The seven metal electrodes are connected with alternating polarities. Electrodes 1, 3, 5, and 7 are electrically connected to the first external lead, and electrode 2, 4, and 6 are electrically connected to the second external lead. Adjacent electrodes are connected to different external leads, thus forming six electrically parallel confined energy absorption units. When an external pulse voltage is applied between the first and second external leads, each confined energy absorption cavity experiences essentially the same pulse voltage. The alternating polarity parallel structure can: increase the effective electrode area of ​​the element; disperse the pulse energy to the six energy absorption cavities; reduce the concentration of energy and temperature rise in a single cavity; improve the utilization rate of material volume; and increase the total energy absorption capacity of the element while maintaining a 10 mm electrode spacing. Under an applied voltage of 1000 V and a plate spacing of 10 mm, the nominal average field strength in a single energy-absorbing cavity is 0.1 kV / mm. This nominal operating field strength is lower than the AC breakdown field strength of approximately 1.85 kV / mm for the packaged element in Example 1. In practical engineering applications, the field strength at the plate edge, the pulse peak value, and the necessary safety margin should still be considered.

[0071] (4) Volume of confined energy-absorbing cavities: The effective nominal area of ​​a single electrode plate is 6624 mm², or 66.24 cm², calculated as 138 mm × 48 mm; the spacing between adjacent electrodes is 10 mm, or 1 cm, so the theoretical volume of a single confined energy-absorbing cavity is approximately 66.24 cm³, or 66.24 mL; the theoretical total volume of the six confined energy-absorbing cavities is approximately 397.44 mL. The above volumes are calculated based on the entire area of ​​the metal electrodes as the effective overlapping area. The actual volume of the energy-absorbing cavities should deduct the volume occupied by the insulating spacer frame, mounting groove, sealing area, and electrode lead-out structure. In this embodiment, the actual volume of a single cavity is 64 mL, and the actual total volume of the six energy-absorbing cavities is 384 mL.

[0072] (5) Material filling: The material is filled under vacuum conditions of -90 kPa (gauge pressure) for 10 min to remove bubbles. During filling, the element is placed vertically or tilted, and the material is slowly injected through the filling port at the bottom or side of the shell. The air in the energy absorption chamber is discharged through the exhaust port at the top of the shell. Low-amplitude vibration or intermittent vacuum-assisted venting can be used during the filling process to allow the material to enter the 6 confined energy absorption chambers in sequence. After confirming that there are no obvious large air bubbles or unfilled areas in each energy absorption chamber and the target filling mass is reached, the filling port and exhaust port are sealed. In this embodiment, the material filling mass of a single element is 500 g, the filling rate is about 85%, and the corresponding material density is about 1.532 g / mL. Connecting holes or guide channels can be set on the insulating spacer frame to allow the slurry to flow between the 6 energy absorption chambers and fill them evenly.

[0073] (6) Insulation Spacing Structure: The 10 mm spacing between adjacent electrode plates is controlled by a polytetrafluoroethylene (PTFE) insulation spacer frame, insulation support column, or internal mounting groove in the housing. The insulation spacing structure also serves to prevent contact between adjacent electrode plates, maintain consistent thickness of each energy-absorbing cavity, limit electrode plate displacement during transportation and pulse action, reduce local field concentration near the electrode plate edges, and provide flow and exhaust channels for slurry filling. In other embodiments, porous PTFE, glass fiber, polyimide porous membrane, or porous ceramic isolation layer can be provided near the electrode plates to reduce the degree of direct contact between the composite particles and the metal electrode plates.

[0074] (7) Sealing Structure: A polytetrafluoroethylene (PTFE) gasket or fluororubber sealing ring is installed between the housing cover and the housing body, and is tightened and fixed by screws around the housing perimeter. The sealing structure is used to prevent water and ethylene glycol from evaporating, to prevent slurry leakage, to prevent external impurities and moisture from entering, and to maintain the stability of the liquid phase composition during the repeated pulse process. If necessary, a two-component epoxy insulating sealant can be applied to the outside of the gasket. An insulating sleeve, sealing ring, and sealant are installed at the location where the external lead-out end passes through the insulating housing to prevent liquid phase leakage along the lead-out end.

[0075] (8) External Lead-Out Terminals and Fixing Structure: The first and second external lead-out terminals are respectively connected to two sets of alternately arranged metal plates and extend to the outside of the insulating housing. The external lead-out terminals can be stud terminals, terminals, plate-shaped lead-out terminals, or clamping leads for the experimental stage. Screw mounting holes are provided at the four corners of the insulating housing for fixing the components to the experimental platform or equipment mounting base; in other embodiments, guide rail mounting, snap-fit ​​fixing, pressure plate fixing, flange connection, or embedded mounting can also be used.

[0076] To verify performance, the following specific examples and comparative examples are provided. In the following examples, unless otherwise specified, the aluminosilicate raw material is kaolin (layered aluminosilicate); the titanium dioxide content is calculated based on the total mass of the aluminosilicate and titanium dioxide composite powder without silicon source interface treatment. In the pulse energy absorption test, the "temperature rise corresponding to 50 J absorbed per milliliter" is calculated based on the effective test volume, total energy, and actual temperature rise of each sample, used for comparison of the same diameter under different pulse numbers and total energy conditions; the conversion formula is: ΔT 50 =ΔT measured × (50V / E), where ΔT 50 The converted temperature rise corresponding to 50 J absorption per milliliter is given by ΔT, which is the actual temperature rise of the sample (K), V, which is the effective volume of the sample (mL), and E, which is the total energy input during the test (J). The effective volume of each sample is based on the actual loading volume or the calibrated effective test volume. The settings for the examples and comparative examples are shown in the table below: Table 2. Examples and Comparative Examples Settings

[0077] Specifically as follows: Example 1 (E1) Approximately 668g of solid-liquid two-phase electro-induced phase change energy-absorbing material was prepared according to the complete process of the specific preparation method provided above. The formulation composition is shown in Table 3 below: Table 3 Raw material formulation composition of Example 1

[0078] The total content of the solid phase component was 60.00 wt% (based on the nominal value of the formulation), the TiO2 content was 20 wt%, and the mass ratio of water to ethylene glycol was 1:1. 80 g of the total ethylene glycol was used for pre-wetting, and the remaining 54 g of ethylene glycol and 134 g of deionized water were added in three separate additions according to the stepwise addition method described above. Approximately 500 g of the resulting material was used to fill the pulse energy-absorbing element (85% fill rate, encapsulated with a two-component epoxy insulating sealant), and approximately 168 g was used for structural characterization and related electrical tests. Example 1 serves as a reference sample for the complete technical solution.

[0079] Example 2 (E2) Example 2 was used to investigate the effect of the total solid content on dielectric properties and pulsed energy absorption temperature rise. Except for the different total solid content, all samples used the same aluminosilicate / TiO2 composite powder, the same silicon source interface treatment process, the same TiO2 content (20 wt%), and the same water-ethylene glycol mass ratio (1:1). Ethylene glycol, equivalent to approximately 30% of the total liquid mass, was used for pre-wetting, and the remaining liquid phase was added in steps. Except for the solid-liquid ratio, the preparation conditions were the same as in Example 1. Each sample was prepared based on the production of 100 g of final material, and the formulations are shown in Table 4 below. Table 4. Raw material composition of each sample in Example 2

[0080] For example, when E2-2 is based on 100 g of final material, 60 g of surface-controlled aluminosilicate / TiO2 composite powder, 20 g of deionized water and 20 g of ethylene glycol are taken, of which about 6 g of ethylene glycol is used for interface pre-wetting and the remaining 14 g of ethylene glycol is added in the subsequent stepwise liquid addition process.

[0081] The pulse energy absorption performance test results of each sample are shown in Table 5 below: Table 5. Test results of pulse energy absorption performance of each sample in Example 2

[0082] As shown in the table above, the lowest temperature rise (9.494 K) corresponding to 50 J is achieved when the total solid content is 60.00 wt%. Temperature rise increases with solid content deviating from 60 wt%. This is because: when the solid content is too low, the number of solid-liquid interfaces is insufficient, limiting the contribution of interfacial polarization to energy dispersion and absorption; when the solid content is too high, the interparticle spacing decreases, increasing the probability of contact and easily forming localized conductive channels, leading to increased dielectric loss and Joule heating. Therefore, the total solid content can be controlled within the range of 50 wt% to 70 wt%, preferably 57 wt% to 63 wt%, and more preferably 60 wt%.

[0083] Reference Figure 2 and Figure 3 Dielectric property tests showed that the dielectric constant and dielectric loss spectrum of the material differed with different solid filler mass fractions. Different solid content corresponded to different numbers of solid-liquid interfaces and interfacial polarization intensities. The 60.00 wt% sample exhibited a relatively moderate dielectric constant and low dielectric loss response, indicating that its interfacial polarization and charge dissipation processes were relatively balanced. The Cole-Cole diagram of complex conductivity showed that the 60.00 wt% sample had higher impedance characteristics, indicating that long-range charge migration was suppressed at this solid content, making it less likely to form through-conductive channels and thus reducing the risk of Joule heat concentration.

[0084] Example 3 (E3) Example 3 investigated the effects of TiO2 functional phase content on the dielectric polarization, conductivity, pulse energy absorption, and temperature rise of the material. A series of samples were prepared with TiO2 contents of 0 wt%, 10 wt%, 20 wt%, 30 wt%, and 40 wt%. Except for the TiO2 content, all samples were prepared under the same conditions: a total solid phase content of 60 wt%, a total liquid phase content of 40 wt%, a water to ethylene glycol mass ratio of 1:1, the same silicon source type and interface treatment conditions, a ethylene glycol pre-wetting ratio of 30% of the total liquid phase, and the same number of stepwise liquid additions and degassing conditions. Each sample was prepared based on 100 g of final material, with 60 g of solid phase and 40 g of liquid phase, including 20 g of water and 20 g of ethylene glycol. The formulations of each sample are shown in Table 6 below. Table 6. Raw material composition of each sample in Example 3

[0085] The pulsed energy absorption test results for each sample are shown in Table 7 below: Table 7. Pulse energy absorption test results for each sample in Example 3

[0086] Test results show that when the TiO2 content increases from 0 wt% to 20 wt%, the temperature rise corresponding to 50 J decreases from 10.2472 K to 9.4940 K, indicating that the appropriate introduction of the TiO2 functional phase can improve the energy dissipation and temperature rise control performance of the material under pulsed electric fields. When the TiO2 content is further increased to 30 wt% and 40 wt%, the temperature rise corresponding to 50 J increases to 11.3646 K and 12.1787 K, respectively, indicating that a higher TiO2 content is not necessarily more beneficial. Excessive TiO2 content may lead to enhanced charge migration between composite particles, weakened interparticle insulation, and local current concentration, thereby increasing the temperature rise during pulsed energy absorption. Under the test conditions in this group, the E3-20 sample with a TiO2 content of 20 wt% has the lowest temperature rise corresponding to 50 J, which is 9.4940 K. Therefore, the preferred TiO2 functional phase content is 20 wt%.

[0087] The resistance and current data show that as the TiO2 content increases, the overall resistance of the sample decreases and the overall current increases, indicating that the TiO2 content affects charge transport and interfacial polarization behavior in the composite system. When the TiO2 content is 20 wt%, the material achieves a good balance between interfacial polarization energy absorption and long-range charge migration suppression.

[0088] Reference Figure 4 Dielectric property tests showed that the dielectric constant and dielectric loss of samples with different TiO2 contents differed significantly with frequency. The sample with a TiO2 content of 20 wt% (SiAl / TiO2 mass ratio of 8:2) exhibited a lower dielectric constant and dielectric loss tangent within the tested frequency range. This indicates that at a TiO2 content of 20 wt%, the dispersion and interfacial isolation of the TiO2 functional phase on the aluminosilicate support framework are more suitable, reducing excessive accumulation of space charge and long-range charge migration at low frequencies, and suppressing local conductive loss and Joule heat concentration. As the TiO2 content further increases, the distance between adjacent TiO2 functional phases shortens, enhancing interfacial charge accumulation and local charge migration, leading to an increase in the low-frequency dielectric constant and a stronger dielectric loss response.

[0089] Reference Figure 5Equivalent series resistance and complex conductivity tests showed that the sample with a TiO2 content of 20 wt% exhibited relatively high impedance and low complex conductivity response within the test frequency range, indicating that long-range charge migration and through-conductivity in this sample were strongly restricted. This may be because the TiO2 functional phase is relatively uniformly dispersed on the aluminosilicate framework and, together with the insulating interface layer, separates the charge migration paths between particles, thus confining the charge response more to the vicinity of particles and the solid-liquid interface, thereby reducing the probability of continuous conductive channels and local Joule heating. When the TiO2 content further increases, the distance between adjacent TiO2 functional phases shortens, local charge migration and hopping conductivity are enhanced, and the complex conductivity response of the material increases.

[0090] Based on the dielectric response, equivalent resistance, pulse temperature rise, and temperature rise corresponding to 50 J of samples with different TiO2 contents, pulse energy absorption effect can be obtained when the content of TiO2 functional phase is 10 wt%~40 wt%, preferably 10 wt%~30 wt%, and more preferably 20 wt%.

[0091] Comparative Example 1 (C1) Comparative Example 1 was used to compare the differences between "TiO2 in-situ loading + silicon source interface control" and ordinary physical blending, focusing on its effects on TiO2 dispersion, dielectric response, and pulse temperature rise. Comparative Example 1 maintained the same final material mass, total solid content, theoretical TiO2 content, water to ethylene glycol mass ratio, powder particle size range, total mixing and shearing time, vacuum degassing conditions, element structure, material filling mass, and pulse testing conditions as Example 1, except that the in-situ loading in step S2 and the silicon source interface control in step S3 were omitted.

[0092] The total solid mass of Comparative Example 1 was 400 g, of which the TiO2 content was 20 wt%. The nano-TiO2 adopted the same or similar crystal form and particle size as the TiO2 formed in situ in Example 1, i.e., anatase nano-TiO2. The preparation method was as follows: 320 g of aluminosilicate powder pretreated in step S1 and 80 g of nano-TiO2 powder were placed in a mixing device and dry-mixed at 800 r / min for 30 min (or ball-milled for 30 min). This step only achieved physical mixing, without adding a titanium source or performing in-situ hydrolysis loading. After mixing, the powder was passed through a 300-mesh standard sieve to obtain a simple physical blend powder. Comparative Example 1 did not undergo TEOS, sodium silicate, or silica sol treatment, and did not form a silicon-oxygen insulating interface layer. Subsequently, 80 g of ethylene glycol was taken and the physical blend powder was pre-wetted at the interface under the same conditions as in Example 1 (30 ℃, -85 kPa gauge pressure, 300 r / min treatment for 20 min, and intermittent ultrasonication at 200 W for 1 min every 5 min); the remaining liquid phase was added in three portions in the same manner as in Example 1; vacuum degassing was performed for 10 min under -90 kPa gauge pressure; 500 g was taken and filled into the same pulse energy absorption element as in Example 1, with the filling rate controlled at 85%, and sealed using the same materials and processes.

[0093] The structural characterization results of Example 1 and Comparative Example 1 are as follows: (1) X-ray diffraction (XRD): Reference Figure 6 Both samples exhibited characteristic diffraction peaks of the TiO2 crystalline phase. Specifically, the sample of Example 1 showed characteristic diffraction peaks of the (101), (004), and (200) crystal planes of anatase TiO2 at approximately 25.3°, 37.8°, and 48.0°, respectively, indicating the formation of anatase TiO2 functional phases after titanium source hydrolysis, aging, and calcination. Compared to the simple physical blend sample, the characteristic diffraction peaks of anatase TiO2 in the sample of Example 1 were clearer, indicating that the TiO2 in it had more obvious crystallization characteristics. The diffraction peak positions of the two samples were generally close, and no obvious new crystalline reaction products were observed, indicating that the silicon source interface treatment did not significantly change the main crystal form of TiO2. No obvious characteristic diffraction peaks of crystalline SiO2 were observed in the sample of Example 1. Combined with the enhanced Si-O-Si characteristic absorption in the following infrared spectral results, it can be considered that the silicon source treatment increased the silicon-oxygen-containing structure in the composite powder, and this structure mainly exists in an amorphous or low-crystallinity state.

[0094] (2) Scanning electron microscope (SEM): Refer to Figure 7The anatase TiO2 raw material powder consists of irregular fine particles and exhibits obvious secondary agglomeration. In Comparative Example 1, multiple coarse blocky or flower-like agglomerates were observed, with relatively clear boundaries between particles of different morphologies, indicating that the aluminosilicate and TiO2 are mainly bonded through physical stacking, with relatively limited particle distribution uniformity. Example 1's sample exhibits an irregular composite aggregate composed of numerous fine particles and an aluminosilicate framework. The particle surface is relatively rough with abundant interparticle porosity, and the number of independent coarse TiO2 agglomerates is relatively reduced. The integration of fine particles with the supporting framework is improved, indicating that titanium source loading treatment and silicon source interface control are beneficial for improving the bonding and distribution of the composite particles. The rough, porous surface of Example 1 provides more solid-solid and solid-liquid interface areas, which is beneficial for the wetting and retention of the composite particles by the water-ethylene glycol solution and helps reduce the risk of local charge migration and Joule heat concentration caused by coarse TiO2 agglomerates.

[0095] (3) Fourier transform infrared spectroscopy (FTIR): Reference Figure 8 Both samples exhibited characteristic absorptions of aluminosilicates (Si-O-Si / Si-O-Al) and TiO2 (Ti-O-Ti). Compared to Comparative Example 1, the sample of Example 1 showed characteristic absorptions at approximately 900 cm⁻¹. - ¹~1200 cm - The Si-O related absorption within the range of ¹ is relatively enhanced and exhibits a certain peak broadening, indicating that the relative content of silicon-oxygen structures or the local chemical environment in the composite powder changes after silicon source interface modulation. The positions of the Ti-O-Ti characteristic absorptions in the two samples are basically consistent, indicating that silicon source treatment did not change the main lattice structure of TiO2. The above results show that TEOS hydrolysis and condensation introduces silicon-oxygen structures on the surface and / or between particles of the composite powder, which is beneficial for adjusting the surface polarity, particle interface state, and contact relationship between the TiO2 functional phase of the composite powder.

[0096] Comparative Example 2 (C2) Comparative Example 2 was used to investigate the effects of ethylene glycol interface pre-wetting and stepwise liquid addition on powder wetting, agglomeration control, bubble removal, liquid phase retention, sedimentation stability, and pulse temperature rise. Comparative Example 2 used the same surface-controlled aluminosilicate / TiO2 composite powder as Example 1, with the same final chemical composition as Example 1. The only difference was that the ethylene glycol pre-wetting step was omitted, and water and ethylene glycol were pre-mixed and added at once.

[0097] The preparation method of Comparative Example 2 is as follows: 134 g of deionized water and 134 g of ethylene glycol were taken and stirred at 800 r / min for 30 min at 30 ℃ to form a uniform water-ethylene glycol composite solution; 400 g of surface-controlled aluminosilicate / TiO2 composite powder was taken without ethylene glycol pre-wetting, and 268 g of water-ethylene glycol composite solution was added to the composite powder in one go within 5 min; to eliminate the influence of shear time difference, after the liquid phase was added at one time, the same shearing program as in Example 1 was adopted (first stage shearing at 2000 r / min for 5 min, second stage shearing at 3500 r / min for 8 min, and third stage shearing at 2500 r / min for 5 min); vacuum degassing was performed for 10 min under a gauge pressure of -90 kPa; 500 g was taken and filled into the same pulse energy absorption element as in Example 1, with the filling rate controlled at 85%, and sealed in the same way.

[0098] The slurry properties of Example 1 and Comparative Example 2 are compared in Table 8 below: Table 8 Comparison of slurry performance between Example 1 and Comparative Example 2

[0099] From Table 8, Figure 9 and Figure 10 As can be seen, the sample of Example 1, which uses ethylene glycol pre-wetting and stepwise liquid addition, has a narrower particle size distribution, lower apparent viscosity and yield stress, lower liquid separation rate and no obvious sedimentation stratification, higher average breakdown field strength at power frequency and less dispersion of breakdown data (larger Weber distribution shape parameter β). This indicates that the pre-wetting and stepwise liquid addition process is beneficial to improving the filling uniformity, degassing quality and storage stability of the high solids content solid-liquid system.

[0100] Furthermore, AC breakdown field strength tests were conducted on the packaged elements of Example 1, Comparative Example 1, and Comparative Example 2. Under the same electrode structure, electrode spacing, material filler, boost rate, and test temperature conditions, the AC breakdown field strength of the packaged element of Example 1 was approximately 1.85 kV / mm, which was significantly higher than approximately 0.85 kV / mm of the packaged element of Comparative Example 1 and approximately 1.18 kV / mm of the packaged element of Comparative Example 2.

[0101] Compared to Comparative Example 1, the AC breakdown field strength of Example 1 was increased by approximately 117.6%. Comparative Example 1 used a simple physical blend of aluminosilicate and TiO2 without TiO2 loading and recombination or silicon source interface modulation. This resulted in TiO2 particles easily forming independent aggregates or directly contacting adjacent particles, leading to uneven particle distribution within the material and potentially creating localized field concentrations and charge migration channels. Example 1, by supporting the TiO2 functional phase with aluminosilicate and introducing a silicon-oxygen insulating interface layer, improved TiO2 dispersion and interparticle insulation, reducing the probability of localized conductive paths and electric field concentrations, thereby increasing the AC breakdown field strength.

[0102] Compared to Comparative Example 2, the AC breakdown field strength of the packaged element in Example 1 was increased by approximately 56.8%. Example 1 and Comparative Example 2 used the same surface-controlled composite powder, solid content, and final water-ethylene glycol ratio. The main difference was that Comparative Example 2 did not perform ethylene glycol interface pre-wetting and added the water-ethylene glycol compound solution all at once. Adding the solution all at once can lead to uneven powder wetting, localized dry powder agglomeration, uneven liquid phase distribution, and residual microbubbles. The dielectric strength of microbubbles and localized interface voids is lower than that of the dense solid-liquid composite region, which can easily cause local field distortion under an AC electric field and become the initiation point of breakdown. Example 1 first pre-wetted the surface-controlled composite powder with ethylene glycol, allowing the high-boiling-point liquid phase to pre-enter the particle surface, pores, and interparticle interface regions. Then, through stepwise liquid addition and vacuum degassing, a high-solids-content confined solid-liquid system was gradually constructed. This helped reduce dry powder agglomeration, interface voids, and residual bubbles, improving the density and interface uniformity of the material filling, thus achieving a higher AC breakdown field strength.

[0103] The withstand voltage cycle stability test (approximately 200 cycles) shows that the breakdown field strength of the three groups of packaged elements, namely Example 1, Comparative Example 1 and Comparative Example 2, does not decrease with the number of cycles. Among them, the breakdown field strength of Example 1 is stable at the highest level among the three groups, indicating that the material of this application can maintain stable performance under repeated pulses.

[0104] Furthermore, the pulse test results of Example 1, Comparative Example 1, a single aluminosilicate sample (SiAl, i.e., E3-0), and a single TiO2 sample are shown in Table 9 below. The single TiO2 sample was prepared by mixing nano-TiO2 powder with the same solid content, the same water-ethylene glycol ratio, and the same degassing process; the pulse test conditions (voltage 1000 V, element structure) were the same for all four groups of samples.

[0105] Table 9. Pulse test results for each sample

[0106] As shown in Table 9, the pulse currents of Example 1 and Comparative Example 1 were 0.096 A and 0.088 A, respectively, and their resistances were 11593.610 Ω and 12748.014 Ω, respectively. Their overall electrical responses were on similar orders of magnitude. The temperature rise of Example 1 corresponding to 50 J per milliliter was 9.494 K, lower than that of Comparative Example 1 (9.871 K), a decrease of approximately 3.82%. This indicates that in-situ loading, silicon source interface control, ethylene glycol pre-wetting, and stepwise liquid addition processes are beneficial for improving the distribution of pulse energy within the material and reducing localized heat concentration. Compared to a single aluminosilicate sample, the calculated temperature rise of Example 1 was reduced by approximately 7.35%; compared to a single TiO2 sample, the calculated temperature rise of Example 1 was reduced by approximately 70.11%, and the pulse current was significantly reduced. The above results indicate that the aluminosilicate support framework can disperse and isolate the functional phase of TiO2, enabling the material to maintain the pulse electric field response while reducing the current concentration and local Joule heating that may occur in the pure TiO2 system.

[0107] It can be seen that the complete technical solution of "in-situ load + insulating interface layer + pre-wetting stepwise liquid addition" significantly improves the breakdown field strength (approximately 117.6% and approximately 56.8%) more than the improvement in steady-state equivalent temperature rise (approximately 3.82%), indicating that the technical effect of this application in suppressing conduction is mainly reflected in the improvement of breakdown field strength and withstand voltage cycle stability. Furthermore, a physical example of a device prepared from the solid-liquid two-phase electroinduced phase change energy-absorbing material according to one embodiment of this application is shown below. Figure 11 As shown.

[0108] The foregoing has shown and described the basic principles, main features, and advantages of this application. Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of this application as claimed. The scope of protection of this application is defined by the appended claims and their equivalents.

Claims

1. A solid-liquid two-phase electro-induced phase change energy-absorbing material, characterized in that, Includes solid phase components and liquid phase components; The solid phase component is a multi-interface composite particle, which includes an aluminosilicate framework, titanium dioxide nanocrystals grown in situ on the surface and / or in the channels of the aluminosilicate framework, and an insulating interface layer covering the outside of the titanium dioxide nanocrystals. The insulating interface layer is a silicon dioxide layer or a silicate layer. The liquid phase component is a water-ethylene glycol compound solution; The solid phase component has a content of 50 wt% to 70 wt%, and the liquid phase component has a content of 30 wt% to 50 wt%. The liquid phase component fills the interfacial region between the multi-interface composite particles to form a confined solid-liquid interfacial phase.

2. The solid-liquid two-phase electro-induced phase change energy-absorbing material according to claim 1, characterized in that, The aluminosilicate framework is a layered aluminosilicate, which is selected from at least one of kaolin, montmorillonite, mica, and attapulgite.

3. The solid-liquid two-phase electro-induced phase change energy-absorbing material according to claim 1 or 2, characterized in that, The mass of the titanium dioxide nanocrystals accounts for 10 wt% to 40 wt% of the total mass of the aluminosilicate framework and the titanium dioxide nanocrystals.

4. The solid-liquid two-phase electro-induced phase change energy-absorbing material according to claim 1 or 2, characterized in that, The mass ratio of water to ethylene glycol in the water-ethylene glycol compound solution is 1:9 to 7:

3.

5. The solid-liquid two-phase electro-induced phase change energy-absorbing material according to claim 1 or 2, characterized in that, The median particle size D50 of the multi-interface composite particles is 0.5 μm to 20 μm.

6. The solid-liquid two-phase electro-induced phase change energy-absorbing material according to claim 1 or 2, characterized in that, The content of the solid phase component is 57 wt% to 63 wt%, and the content of the liquid phase component is 37 wt% to 43 wt%.

7. A method for preparing a solid-liquid two-phase electro-induced phase change energy-absorbing material, characterized in that, Includes the following steps: S1: Pre-treat the aluminosilicate raw material to obtain aluminosilicate framework powder; S2: The aluminosilicate framework powder is dispersed in a titanium source hydrolysis system, and after hydrolysis, aging and calcination crystallization, titanium dioxide nanocrystals are grown in situ on the surface and / or pores of the aluminosilicate framework powder to obtain aluminosilicate-titanium dioxide composite particles. S3: The aluminosilicate-titanium dioxide composite particles are hydrolyzed and condensed to form an insulating interface layer on the outside of the titanium dioxide nanocrystals using a silicon source, and then dried to obtain multi-interface composite particles. S4: The multi-interface composite particles are mixed with a water-ethylene glycol compound solution, and then sheared, dispersed and degassed under vacuum to obtain the solid-liquid two-phase electro-phase change energy-absorbing material as described in any one of claims 1 to 6.

8. The preparation method according to claim 7, characterized in that, In step S2, the titanium source in the titanium source hydrolysis system is tetrabutyl titanate or titanium oxysulfate; the loading, crystal ratio and grain size of the titanium dioxide nanocrystals are controlled by adjusting the titanium source concentration, hydrolysis pH, aging time and calcination temperature.

9. The preparation method according to claim 7 or 8, characterized in that, In step S3, the silicon source is sodium silicate or tetraethyl orthosilicate; the thickness of the insulating interface layer is controlled by adjusting the amount of silicon source and the hydrolysis conditions.

10. The application of the solid-liquid two-phase electro-phase change energy-absorbing material as described in any one of claims 1 to 6 in converter valves, flexible power transmission and transformation equipment, power electronic devices, pulse overvoltage protection devices, or overvoltage protection of electrical equipment.